Doing gender in conflict talk: an analysis of gendered discourses in a U.S. reality TV show - Sung, Chit Cheung Matthew (Journal of English Studies, 2013)
This paper presents an analysis of gendered discourses in conflict talk by drawing upon interactional data from the U.S. reality TV show The Apprentice. It explores the ways in which women professionals enact their gender identities while engaging actively in conflict talk which is stereotypically coded as ‘masculine’. Specifically, I shall look at the different ways in which they construct their gendered identities by aligning themselves with different gendered discourses. It is found that these woman professionals are shown to draw upon different gendered discourses in constructing their feminine gender identities, namely the dominant discourses of femininity and resistant discourses. The paper also shows that the enactment of gendered identities in conflict talk may vary from one context to another.